Subcellular Localization of Class I Histone Deacetylases in the Developing Xenopus tectum - Guo, Xia; Ruan, Hangze; Li, Xia; Qin, Liming; Tao, Yi; Qi, Xianjie; Gao, Juanmei; Gan, Lin; Duan, Shumin; Shen, Wanhua (Frontiers in Cellular Neuroscience, 2016)
Histone deacetylases (HDACs) are thought to localize in the nucleus to regulate gene transcription and play pivotal roles in neurogenesis, apoptosis and plasticity. However, the subcellular distribution of class I HDACs in the developing brain remains unclear. Here, we show that HDAC1 and HDAC2 are located in both the mitochondria and the nucleus in the Xenopus laevis stage 34 tectum and are mainly restricted to the nucleus following further brain development. HDAC3 is widely present in the mitochondria, nucleus and cytoplasm during early tectal development and is mainly distributed in the nucleus in stage 45 tectum. In contrast, HDAC8 is broadly located in the mitochondria, nucleus and cytoplasm during tectal development. These data demonstrate that HDAC1, HDAC2 and HDAC3 are transiently localized in the mitochondria and that the subcellular distribution of class I HDACs in the Xenopus tectum is heterogeneous. Furthermore, we observed that spherical mitochondria accumulate in the cytoplasm at earlier stages, whereas elongated mitochondria are evenly distributed in the tectum at later stages. The activity of histone acetylation (H4K12) remains low in mitochondria during tectal development. Pharmacological blockades of HDACs using a broad spectrum HDAC inhibitor of Trichostatin A (TSA) or specific class I HDAC inhibitors of MS-275 and MGCD0103 decrease the number of mitochondria in the tectum at stage 34. These findings highlight a link between the subcellular distribution of class I HDACs and mitochondrial dynamics in the developing optic tectum of Xenopus laevis.